The Influence of Organizational Climate, Technical Competence, and Work Motivation on Employee Performance at the Population Control, Family Planning, Women's Empowerment, and Child Protection Offices Boyolali Regency - Heni Widihastuti; Rini Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study seeks to examine and assess the impact of organizational environment, technical competence, and work motivation on employee performance at the Population Control, Family Planning, Women's Empowerment, and Child Protection Offices. The study design employs a causal quantitative methodology to ascertain the impact of the examined factors. The data collecting instrument employs validated and reliable questionnaires delivered to staff of the Population Control, Family Planning, Women's Empowerment, and Child Protection Offices. The sample analyzed in this research comprised 70 workers. This study used a saturation sampling strategy, utilizing all members of the population as samples. Data analysis was conducted via SPSS 26. The study's results indicate that the organizational atmosphere positively and significantly affects employee performance. Technical proficiency exerts a favorable and substantial impact on employee performance. Work motivation has a favorable and substantial impact on employee performance.